Umbelliferone Inhibits Spermatogenic Defects and Testicular Injury in Lead-Intoxicated Rats by Suppressing Oxidative Stress and Inflammation, and Improving Nrf2/HO-1 Signaling - Alotaibi MF; Al-Joufi F; Abou Seif HS; Alzoghaibi MA; Djouhri L; Ahmeda AF; Mahmoud AM (Dove Medical Press, 2020)
Mohammed F Alotaibi,1 Fakhria Al-Joufi,2 Howida S Abou Seif,3 Mohammed A Alzoghaibi,1 Laiche Djouhri,4 Ahmad F Ahmeda,5 Ayman M Mahmoud6 1Physiology Department, College of Medicine, King Saud University, Riyadh 11461, Saudi Arabia; 2Department of Pharmacology, Faculty of Pharmacy, Jouf University, Sakaka 2014, Saudi Arabia; 3Medical Physiology Department, Medical Research Branch, National Research Centre, Giza 12622, Egypt; 4Department of Basic Medical Sciences, College of Medicine, Qatar University, Doha 2713, Qatar; 5College of Medicine, Ajman University, Ajman 346, United Arab Emirates; 6Physiology Division, Zoology Department, Faculty of Science, Beni-Suef University, Beni-Suef 62514, EgyptCorrespondence: Ayman M MahmoudPhysiology Division, Zoology Department, Faculty of Science, Beni-Suef University, Beni-Suef 62514, EgyptTel +201278355478Email ayman.mahmoud@science.bsu.edu.egIntroduction: Lead (Pb) is an environmental toxic metal that threatens human health. Umbelliferone (UMB) is a coumarin with known medicinal and protective properties against cytotoxicity. This study explored the ameliorative effect of UMB against Pb-induced testicular toxicity in rats, focusing on steroidogenesis, oxidative stress and inflammation.Materials and Methods: Rats received lead acetate (50 mg/kg) and UMB (25, 50 or 100 mg/kg) via oral gavage for 4 weeks.Results: Pb-intoxicated rats exhibited testicular tissue injury and decreased serum levels of LH, FSH and testosterone. The count, viability, motility and normal morphology of the sperms were decreased accompanied with downregulated steroidogenesis markers in Pb-induced group. UMB prevented testicular injury, increased serum levels of LH, FSH and testosterone, upregulated steroidogenesis markers and improved the semen quality. In addition, UMB attenuated oxidative stress and oxidative DNA damage, downregulated the expression of pro-inflammatory mediators and Bax, boosted antioxidant defenses and Bcl-2, and upregulated Nrf2/HO-1 signaling in Pb-intoxicated rats.Conclusion: UMB prevents Pb-induced testicular injury by suppressing oxidative damage, inflammation and cell death, and boosting antioxidant defenses, Nrf2/HO-1 signaling and pituitary-gonadal axis. Thus, UMB may represent a protective and cost-effective agent against Pb testicular toxicity, pending further investigations to elucidate other underlying mechanisms.Keywords: umbelliferone, StAR, oxidative stress, Nrf2, inflammation, pituitary-gonadal axis